Approaches to Self‐Management in Chronic Illness. Issue 2 (22nd March 2013) - Novak, Marta; Costantini, Lucia; Schneider, Sabrina; Beanlands, Heather
Abstract Management of a chronic medical condition is a complex process and requires coordinated action between healthcare providers and patients. This process is further complicated by the fact that an increasing number of patients suffer from multiple chronic conditions. Self‐management involves active participation of the patients in the everyday care of the symptoms of their illness(es) and medical treatments, as well as maintaining general health and prevention of progression of medical conditions. Managing the psychosocial consequences of illness is also an important component of self‐management. Data have demonstrated that enhancing self‐management improves quality of life, coping, symptom management, disability, and reduces healthcare expenditures and service utilization. To foster self‐management, potential barriers to implementation as well as facilitators and supports for this approach must be acknowledged. In this article, we review various aspects of self‐management in chronic illness, focusing on chronic kidney disease. Better understanding of these concepts will facilitate patient–provider collaboration, improve patient care with increased patient and staff satisfaction, and may ultimately result in better clinical outcomes and enhanced quality of life for both the patients and their families.